Efforts to Protect Violence in the Households during Covid-19 in Indonesia - Mukidi (2021)
The social distancing appeal that the government encourages is not matched by the state's efforts to provide economic security to the community. PSBB will directly or indirectly limit the movement of the community. The teaching and learning process at schools and residents who work will be limited to working or studying at home. This limitation of activities in public spaces will have an impact on people's income, especially those in the middle to lower economy. The implementation of social distancing during the Covid-19 outbreak has increased the risk of violence against women, complicates women's economic conditions, and affirms women's social status as subordinate, or women are in a lower position than men. The formulation of the problem in this research is what is the cause of domestic violence during the covid-19 period in Indonesia, what are the prevention efforts against domestic violence during the covid-19 period. Causes of Domestic Violence During the Covid-19 Period, namely the government's appeal to the community “at home alone”, causing a separate polemic for women and children, especially those who experience economic and psychological pressure at home from extraordinary isolation measures, has prompted increasing instances of reports of domestic violence, especially women who are forced to live for months in abusive relationships. causes and consequences of violence and to prevent the occurrence of violence through primary prevention programs, policy intervention and advocacy as well as information programs and supporting initiatives through all mass media TV, social networks, cell phones